When social support is not enough: Trauma and PTSD symptoms in a risk-sample of adolescents. (October 2017) - Pinto, Ricardo J.; Morgado, Diogo; Reis, Sara; Monteiro, Rita; Levendosky, Alytia; Jongenelen, Inês
Abstract: Social support can mitigate the severity of posttraumatic stress disorder (PTSD) in children and adults following traumatic events. However, little is known about the role of social support in high-risk samples of adolescents from the community. The present study examined the relationship between social support and PTSD symptoms in adolescents exposed to traumatic events and childhood adversity, after adjusting for the effects of potential covariates, including sociodemographic factors, previous childhood adversity, level of exposure, comorbid anxiety, depression symptoms, and substance abuse, and coping strategies. Method: The participants of the study were 183 adolescents, mean age of 16 years old (M = 15.71, SD = 1.31), ranged between 13 and 17 years old, 89 (48.6%) males and 94 (51.4%) females. Results: The results revealed that 26.2% of the sample met the criteria for probable PTSD. Our statistical model explained 64% of the variance in PTSD symptoms, but social support was not significant after adjusting for covariates. This study found that social support was not enough to reduce PTSD symptoms in adolescents exposed to trauma and adversity. Programs focused only on improving social support may not be effective in reducing mental health symptoms for adolescents, particularly when there has been severe and/or multiple forms of childhood adversity.